Analysis of Encrypted data using DNA Cryptography and Chaotic Systems - Dhakal, Madhav; Shakya, Subarna (Journal of Physical and Life Sciences, 2025)
In the modern world of technology, ensuring security of information is essential for security in both transmitter and receiver of data. In this work, to achieve the goal hybridization concept of DNA based cryptography and chaotic system is implemented. This involves converting binary data to DNA bases, followed by transcription from DNA to mRNA, translation from mRNA to tRNA, and finally, transforming tRNA into reverse tRNA along with this chaotic sequence generated from initial values of chaotic system is implemented to generate the permutation value. Here, the encryption method supports each block sizes of 256 bits and results during the algorithm implementation demonstrated strong security, with an average avalanche effect 76.64%, indicating high sensitivity while key changes. Even a tiny modification to the key value can render the plain message undecryptable, thereby maintaining the confidentiality of the message. Overall, algorithm proposed in this study enhances the security of data transmission over untrusted public networks, offering robust encryption methods that are resistant to modern attacks. Key stakeholders include data security professionals, policymakers, and all individuals who are interested in sending and receiving private data with confidentiality and integrity.